Do Drug Accessibility and OOP Burden Affect Health-Related Quality of Life of Patients With Chronic Diseases? - EQ-5D-5L Evaluation Evidence From Five Districts in China - Shaoliang Tang; Ying Gong; Meixian Liu; Duoer Yang; Kean Tang (Frontiers Media S.A., 2021)
Purpose: The dependence of patients with chronic diseases on drugs may affect their health-related quality of life (HRQoL). This study aims to assess the relationship between the direct economic burden caused by out-of-pocket (OOP) payments, drug accessibility, sociodemographic characteristics, and health-related quality of life.Methods: 1,055 patients with chronic diseases from Gansu, Hebei, Sichuan, Zhejiang, and Tianjin were investigated. Data collection included basic conditions and economic and health insurance conditions of patients with chronic diseases. The CLAD and Tobit regression models were used to analyze and compare the health-related quality of life and influencing factors of patients with chronic diseases in five districts. Differentiated analysis was conducted through sub-sample regression to explore the variable health effects of patients with single and multiple diseases.Results: A total of 1,055 patients with chronic diseases participated in the study, 54.4% of whom were women. The overall average utility score was 0.727, of which Sichuan Province was the highest with 0.751. Participants reported the highest proportion of pain/discomfort problems, while patients reported the least problems with self-care. The improvement of drug accessibility and the reduction of the burden of out-of-pocket expenses have significant positive effects on HRQoL. Various sociodemographic factors such as age and gender also have significant impact on HRQoL of patients with chronic diseases. HRQoL of patients with multiple chronic diseases is more affected by various influencing factors than that of patients with single disease.Conclusion: In order to improve the quality of life of patients with chronic diseases, it is of great importance to ensure the accessibility of drugs and reduce patients' medication burden. Future focus should shift from preventing and controlling chronic diseases as individual diseases to meeting the comprehensive health needs of people suffering from multiple diseases.